Resilience Dalam Exercise Pada Pelanggan Reguler Core Studio Menteng Di Jakarta - Eliza Ganesha Berlian Hutapea; Rilla Sovitriana (Psikologi Kreatif Inovatif, 2022)
This research aims to determine the relationship of self-efficacy and self-regulation withresilience in regular customers of Core Studio Menteng. The sampling technique usessimple random sampling with a try out sample of 30 respondents and then a main data of 20respondents. Data retrieval using Likert scale consists of self-efficacy scale, self-regulationscale, and resilience scale using SPSS (Statistical Package for the Social Science) program 22.0version for Windows. The results of technical analysis of bivariate correlation showed asignificant relationship with a positive direction between self-efficacy and resilience, in whichacquired correlation coefficient (rx1y) of 0.635, as well as a significant relationship with thepositive direction between self-regulation and resilience in which acquired thecorrelation coefficient (rx2y) of 0.660. Furthermore, the multivariate correlationhypothesis test shows that there is a significant relationship with the positive directionbetween self-efficacy and self- regulation with the resilience, with R 0.682. Then, based onstepwise method in looking for the contribution of an independent variable, the result in theoutput indicates that the self-regulation is the only variable which appears as a dominantvariable affecting the resilience variable, while the self-efficacy variable does not appear. Thisindicates that based on the analysis results, R square of 0.466, thereby concluded that thecontribution of Self-Regulation variable simultaneously has a contribution amount of46.6%, while 53.4% is from another factor that includes self-efficacy and factors that are notresearched by researcher. Then to see the results of the non-dominant contribution of theself-efficacy variable, the results of the R Square from the results of the multivariatecorrelation process are reduced by the R Square Change in the results of the stepwise methodprocess, which is 0.466 - 0.463 = 0.030. Based on the results of the analysis, thecontribution of the self-efficacy variable is 0.03%. If the results of R Square Change <0.4%, thenthe results are declared not dominant in influencing the resilience variable.